Modelling Financial Satisfaction Across Life Stages: A Latent Class Approach - Brown, S.; Durand, Robert; Harris, Mark; Weterings, T. (Elsevier, 2014)
We explore the determinants of financial satisfaction using a modelling framework which allows the drivers of financial satisfaction to vary across life stages. Given that financial satisfaction is measured as an ordered variable, our modelling approach is based on a latent class ordered probit model with an ordered probit class assignment function. Our analysis of household survey data indicates that four life stages are supported by the data. Our results suggest that such flexibility is important in understanding the drivers of financial satisfaction over the life cycle since there is a substantial amount of parameter heterogeneity across the four classes.